New variochelins from soil-isolated Variovorax sp. H002 - Haedar, Jabal Rahmat; Yoshimura, Aya; Wakimoto, Toshiyuki (Beilstein Journal of Organic Chemistry, 2024)
The soil bacterial genus Variovorax produce distinct photoreactive siderophores that may play a crucial role in the iron cycle within the rhizosphere. This study focused on exploring the natural products of the soil-isolated Variovorax sp. H002, leading to the isolation of variochelins A–E (1–5), a series of lipohexapeptide siderophores. NMR and MS/MS analyses revealed that these siderophores share a common core structure – a linear hexapeptide with β-hydroxyaspartate and hydroxamate functional groups, serving in iron-binding coordination. Three new variochelins C–E (3–5) were characterized by varied fatty acyl groups at their N-termini; notably, 4 and 5 represent the first variochelins with N-terminal unsaturated fatty acyl groups. Furthermore, the variochelin biosynthetic gene cluster was identified through draft genome sequencing and gene knockout experiments. Compounds 1–5 exhibited antimicrobial activities against Gram-negative bacteria, including several soil-isolated plant pathogens.
Keywords: antimicrobial activity; siderophore; variochelin; Variovorax